Human-computer interaction via hand gesture and pose recognition - Yap, Xian Wei (2016)
This project was carried out to show the human-computer interaction via hand gestures and pose recognition and how it can be a more natural way of interaction. A game application where the navigation and game play can all be controlled just by using hand movements and gestures have been created to demonstrate the project topic. Software such as Unity 3D game engine, Kinect Software Development Kit and SketchUp modelling tool, and hardware like Kinect Xbox 360 sensor have been used throughout the duration of project. These equipments help facilitate the creation of the game application and the implementation of hand gestures.